2006
DOI: 10.1523/jneurosci.0332-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

A Role for  1 Tubulin-Expressing Muller Glia in Regeneration of the Injured Zebrafish Retina

Abstract: ␣1 tubulin (␣1T) is a neuron-specific microtubule protein whose expression is induced in the developing and regenerating CNS. In the adult CNS, ␣1T expression remains high in neural progenitors. Transgenic zebrafish harboring a 1.7 kb ␣1T promoter fragment along with the first exon and intron express the transgene in a manner that recapitulates expression of the endogenous gene. We recently showed that this promoter mediates gene induction in retinal ganglion cells during optic nerve regeneration and in a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
569
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(593 citation statements)
references
References 44 publications
24
569
0
Order By: Relevance
“…Recent experimental evidence suggests that a subset of the Muller glia constitute an INL population of progenitor cells in fish and other vertebrates (Bernardos, et al, 2007;Fausett and Goldman, 2006;Fimble, et al, 2007;Reh, 2001 &Ooto, et al, 2004;Yurco and Cameron, 2005). In teleosts including zebrafish, mechanical damage, chemical toxicity, and phototoxicity stimulated an increase in proliferation of cells in the INL and ONL (Fausett and Goldman, 2006;Vihtelic and Hyde, 2000;Vihtelic, et al, 2006;Wu et al, 2001).…”
Section: Stem Cells and Photoreceptor Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experimental evidence suggests that a subset of the Muller glia constitute an INL population of progenitor cells in fish and other vertebrates (Bernardos, et al, 2007;Fausett and Goldman, 2006;Fimble, et al, 2007;Reh, 2001 &Ooto, et al, 2004;Yurco and Cameron, 2005). In teleosts including zebrafish, mechanical damage, chemical toxicity, and phototoxicity stimulated an increase in proliferation of cells in the INL and ONL (Fausett and Goldman, 2006;Vihtelic and Hyde, 2000;Vihtelic, et al, 2006;Wu et al, 2001).…”
Section: Stem Cells and Photoreceptor Regenerationmentioning
confidence: 99%
“…In teleosts including zebrafish, mechanical damage, chemical toxicity, and phototoxicity stimulated an increase in proliferation of cells in the INL and ONL (Fausett and Goldman, 2006;Vihtelic and Hyde, 2000;Vihtelic, et al, 2006;Wu et al, 2001). Taking advantage of transgenic lines and cell specific labeling, recent analysis revealed that initially many of the proliferating cells had gene expression profiles consistent with Muller glia (Bernardos, et al, 2007;Fausett and Goldman, 2006;Yurco and Cameron, 2005). The dividing cells appeared to migrate to the ONL before differentiating into rods and cones.…”
Section: Stem Cells and Photoreceptor Regenerationmentioning
confidence: 99%
“…This proliferative activity has also been observed following a surgical lesion, and in this case, the nuclei of Müller glia were seen to migrate in a manner reminiscent of interkinetic nuclear migration seen in embryonic neural progenitor cells . Finally, in the zebrafish, proliferating Müller glia have been shown to generate neurons, as well as additional glia, following injury (Fausett and Goldman, 2006). This was demonstrated through cell lineage tracing methods with transgenic zebrafish in which the transgene is expressed in a subset of Müller glia.…”
Section: B Stem Cells and Developmental Genetics Of Regenerationmentioning
confidence: 99%
“…The neural stem cells in the retina arise from differentiated Müller glia, which respond to local retinal injuries by dedifferentiation, proliferation, and production of multipotent neuronal progenitors (retinal stem cells) that can regenerate all types of retinal neurons (17)(18)(19). To discover genes expressed in injury-activated neurogenic Müller glial cells that activate stem cell properties and trigger a neurogenic program, we generated transcriptional profiles of isolated fluorescent-tagged Müller glial cells from light-lesioned adult transgenic zebrafish retinas during the early stages of photoreceptor regeneration.…”
mentioning
confidence: 99%